Diversity of Endophytic Fungi in The Twigs and Roots of Baccaurea brevipes Hook.f. in Langsa Protected Forest, Aceh, Indonesia - Wibowo, Sara Gustia; Navia, Zidni Ilman; Harmawan, Tisna; Dwitya, Yonadiah; Lestari, Ratna; Fadhliani, Fadhliani (JURNAL BIOLOGICA SAMUDRA, 2025)
The Baccaurea brevipes Hook.F. plant has been studied in the past and has the potential to be a therapeutic herb. The Tampoi plant (B. brevipes) has been used as a medication by the Acehnese to regulate menstruation and make urinating easier. In nature, endophytic fungi are widespread and can be easily found in plant tissue. Without infecting the host plant, the endophytes colonize the inter and intracellular spaces of the tissue. Endophytic fungi can create bioactive chemicals that may be similar to or distinct from those of their host plants and have pharmacological effects. However, no studies have been done on its endophytic fungus as a potential source for novel medication development. This study was done to look into endophytic fungi in Baccaurea's twigs and roots. The techniques employed in this study were endophytic fungi purification, identification of macroscopic and microscopic endophytic fungi, and endophytic fungi isolation. Five isolates were identified as a result of isolation and purification; they were designated as isolates BVA1, BVA2, BVA3, BVR1 and BVR2. The genera Neofusicocum sp., Colletotrichum sp., Mucor sp., Fusarium sp. and Schizophyllum sp. are assumed to be the kind of endophytic fungal isolates BVA1, BVA2, BVA3, BVR1 and BVR2.